2000
DOI: 10.1094/pdis.2000.84.7.773
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Swiss Needle Cast in Forest Plantations of Douglas-fir in Coastal Oregon

Abstract: An epidemic of Swiss needle cast, caused by the ascomycete Phaeocryptopus gaeumannii, is causing defoliation and growth reductions in Douglas-fir forest plantations along the Oregon Coast. The area of symptomatic plantations has been monitored annually since 1996 by aerial survey; in spring 1999, 119,500 ha were affected. Pathogen and symptom development have also been monitored on nine permanent plots in stands of differing disease severity. Infection levels and symptom severity are greatest in low elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
159
2
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(176 citation statements)
references
References 4 publications
(5 reference statements)
4
159
2
7
Order By: Relevance
“…However, plots with higher level of foliage retention tended to have a greater proportion of foliage in their litterfall because crown recession (branch mortality) was slower than on plots with low foliage retention [65]. Fogel and Hunt [15] reported that total litterfall wasspring when spores are released from pseudothecia in the stomates of older infected needles and are carried by wind and rain to newly emerged needles [21]. The spores germinate on the surface of a new needle, enter through the stomates, and grow in the intercellular spaces of the leaf tissue until pseudothecia begin to appear in the fall [21].…”
Section: Amountmentioning
confidence: 99%
See 2 more Smart Citations
“…However, plots with higher level of foliage retention tended to have a greater proportion of foliage in their litterfall because crown recession (branch mortality) was slower than on plots with low foliage retention [65]. Fogel and Hunt [15] reported that total litterfall wasspring when spores are released from pseudothecia in the stomates of older infected needles and are carried by wind and rain to newly emerged needles [21]. The spores germinate on the surface of a new needle, enter through the stomates, and grow in the intercellular spaces of the leaf tissue until pseudothecia begin to appear in the fall [21].…”
Section: Amountmentioning
confidence: 99%
“…Fogel and Hunt [15] reported that total litterfall wasspring when spores are released from pseudothecia in the stomates of older infected needles and are carried by wind and rain to newly emerged needles [21]. The spores germinate on the surface of a new needle, enter through the stomates, and grow in the intercellular spaces of the leaf tissue until pseudothecia begin to appear in the fall [21]. Needles are shed when about 50% of stomata are occluded by pseudothecia [21].…”
Section: Amountmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, this foliar disease has intensified in older, naturally established stands as well. Whereas effects on growth (Hansen et al, 2000;Maguire et al, 2002) and physiology (Manter et al, 2000) have been reported, there is very little information available about its effect on wood properties. Anecdotal observations suggest that SNC increases the proportion of latewood relative to earlywood; this shift in early/latewood proportion would be a logical outcome given that previous experimental work has demonstrated that the earlywood production is mostly dependent on old foliage and the latewood mostly on the new foliage (Onaka, 1950).…”
Section: Introductionmentioning
confidence: 99%
“…The pseudothecia emerge through the stomates and release spores in the spring and early summer. The amount of fungus and number of pseudothecia increase with age of the needle until the needle is dropped (Hansen et al, 2000). In heavily infected stands, first-year needles become chlorotic the following spring and drop from the tree during the second growing season.…”
Section: Introductionmentioning
confidence: 99%